1996
DOI: 10.1111/j.1651-2227.1996.tb14033.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fentanyl administration on general and cerebral haemodynamics in sick newborn infants

Abstract: Despite the wide use of fentanyl for analgesia in newborns, concerns have been raised about potential haemodynamic side-effects. Since sick newborns may lose their cerebral blood flow autoregulation, a drug-induced haemodynamic instability could lead to brain injury. We assessed the effects of a 15-min infusion of fentanyl (3 micrograms/kg) on the general and cerebral haemodynamics in 15 newborns (median gestational age 29 weeks, 25th-75th percentile, range 28-31 weeks; birthweight 1170 g, range 955-1790 g). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…For anaesthesia, we used a single dose of fentanyl. Our experimental and clinical experience confirms the information in the scientific literature that a single dose of fentanyl at 3.0 µg/kg minimally affects blood circulation (Hamon et al 1995). Dynamic pulmonary indices in spontaneously breathing animals were calculated based on the data measured after a transitional connection of experimental piglets to the respiratory device.…”
supporting
confidence: 75%
“…For anaesthesia, we used a single dose of fentanyl. Our experimental and clinical experience confirms the information in the scientific literature that a single dose of fentanyl at 3.0 µg/kg minimally affects blood circulation (Hamon et al 1995). Dynamic pulmonary indices in spontaneously breathing animals were calculated based on the data measured after a transitional connection of experimental piglets to the respiratory device.…”
supporting
confidence: 75%
“…The degree and timing of change in cerebral rSO 2 may also be dependent on the extent and duration of decreased left ventricular cardiac function following surgical ligation [28,29] . The effect of sedation during surgery on rSO 2 may be minimal, although literature around alteration of cerebral hemodynamics after sedation in newborns is limited [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Its impact on cerebral and systemic hemodynamics was studied with a short-term infusion in 15 preterm infants, and there were no significant changes in the systemic or cerebral perfusion or pressure. 28 Although fentanyl as a single agent in intubation has not been studied, a cohort study of 33 preterm and term infants intubated after a combination of atropine, fentanyl, and a paralytic agent showed that fentanyl had no significant adverse effects. 7 Remifentanil, another synthetic opiate, has a rapid onset of action and an ultrashort duration of action and has been shown to be a useful drug for neonatal intubation.…”
Section: Analgesiamentioning
confidence: 99%